Rational behaviour, risk aversion: High stakes for society - André de Palma (Organisation for Economic Co-operation and Development (OECD), Joint Transport Research Centre (JTRC), 2008)
Certain areas related to the topics under discussion here lie outside my field; for instance the evaluation of risk assessment and security deficiencies in the transport sector. What has convinced me of the importance of this subject are a few very general conclusions, indeed I would say, impressions, that I have drawn from the truly remarkable development of our powers to analyse the risk decision-making process over some years now. In this paper, the term uncertainty is often used with reference to the management of risks arising from intentionally malicious acts3. The costs of security in this sense of the term are an element of every transport budget today. In addition to the costs of prevention, surveillance and forecasting, the costs of the potential damages arising from such acts will also have to be taken into consideration from this point onwards. The events of 11 September 2001, which accelerated this trend, should suffice to convince us that, from now on, the consequences of such damages will be on a scale comparable to the costs of war. (...)
Keywords: 330